Multiwavelength Analysis of the Intriguing GRB 061126: The Reverse Shock Scenario and Magnetization - Gomboc, A.; Kobayashi, S.; Guidorzi, C.; Melandri, A.; Mangano, V.; Sbarufatti, B.; Mundell, C.; Schady, P.; Smith, R.; Updike, A.; Kann, D.; Misra, K.; et al. (Institute of Physics Publishing, Inc., 2008)
We present a detailed study of the prompt and afterglow emission from Swift GRB 061126 using BAT, XRT,UVOT data and multicolor optical imaging from 10 ground-based telescopes. GRB 061126 was a long burst(T90 ¼ 191 s) with four overlapping peaks in its -ray light curve. The X-ray afterglow, observed from 26 minutes to20 days after the burst, shows a simple power-law decay with X ¼ 1:290 0:008. Optical observations presentedhere cover the time range from 258 s (Faulkes Telescope North) to 15 days (Gemini North) after the burst; the decayrate of the optical afterglow shows a steep-to-shallow transition (from 1 ¼ 1:48 0:06 to 2 ¼ 0:88 0:03) approximately13 minutes after the burst.We suggest the early, steep component is due to a reverse shock and show thatthe magnetic energy density in the ejecta, expressed as a fraction of the equipartition value, is a few 10 times largerthan in the forward shock in the early afterglow phase. The ejecta might be endowed with primordial magnetic fieldsat the central engine. The optical light curve implies a late-time break at about 1.5 days after the burst, while there is noevidence of the simultaneous break in the X-ray light curve. We model the broadband emission and show that someafterglow characteristics (the steeper decay in X-ray and the shallow spectral index from optical to X-ray) are difficultto explain in the framework of the standard fireball model. This might imply that the X-ray afterglow is due to anadditional emission process, such as late-time central engine activity rather than blast-wave shock emission. Thepossible chromatic break at 1.5 days after the burst would give support to the additional emission scenario.